A Review on Some Rhetorical Devises Employed in Political Novels - Omar Adeeb Ghanim (Goodwood Publishing, 2026)
Purpose: This study aims to examine how rhetorical devices function in political novels to construct ideology and influence readers’ perceptions using a Critical Discourse Analysis (CDA) approach. Research Methodology: A qualitative method was employed by analyzing selected excerpts from All the King’s Men and The People’s Choice. This study focuses on identifying rhetorical devices such as metaphors, contrastive pairs, three-part lists, and religious and historical symbols, and interpreting their ideological roles. Results: The findings indicate that rhetorical devices are systematically used to reinforce ideological meanings, evoke emotional responses, and shape readers’ interpretations of political reality. These strategies demonstrate a strong relationship between linguistic choices and the construction of power and persuasion in literary discourses. Conclusions: The study concludes that rhetorical devices function as powerful tools for persuasion and ideological construction rather than merely stylistic features in political novels. Limitations: This research is limited to two novels and a qualitative interpretive approach, which may restrict broader generalization across different literary and cultural contexts. Contributions: This study contributes to discourse analysis and literary studies by emphasizing the importance of rhetorical language in shaping ideology and encouraging critical awareness among readers when interpreting political texts.